Influence of AI literacy and 21st-century skills on the acceptance of generative artificial intelligence among college students - Salhab, Reham; Aboushi, Mosab M. (Frontiers in Education, 2025)
IntroductionFostering Artificial Intelligence (AI) literacy and equipping college students with 21st-century skills in the generative AI era have become a global educational priority. In this context, generative AI offers opportunities for development in higher education institutions. Thus, this study investigates the influence of AI literacy and 21st-century skills on generative AI acceptance.MethodsFor data collection, the study employed a quantitative design with three scales, and the study sample included 260 college students selected randomly.ResultsResults revealed that AI literacy and 21st-century skills are present at a moderate level among college students. AI literacy and 21st-century skills influence the generative AI Acceptance level.DiscussionBased on the results, the study recommends enriching the curriculum with AI literacy and equipping students with 21st-century skills while using generative AI applications.